(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Surgical site infection is a devastating problem for the patient, as well as for the hospital unit where it is found, with increased morbidity and mortality. One of the current methods in the treatment of infected wounds (I.S.Q) is the vacuum closure system or V.A.C. It has been shown that, with the vacuum suction system, wound healing is accelerated with this, the hospital stay decreases, as well as the cost of healing supplies (antiseptics, hydrocolloids, alginates, antibiotic cream, etc.) and of systemic antibiotics used in the healing process. In the study of 92 patients who used the vacuum system or V.A.C, 91% of the patients showed improvement or healing with the use of this system.